Effect of BLV Infection on the Immune Function of Polymorphonuclear Neutrophil in Dairy Cows - Lv, Guanxin; Wang, Hai; Wang, Jianfa; Lian, Shuai; Wu, Rui (Frontiers in Veterinary Science, 2021)
Enzootic bovine leukemia is a late-onset, neoplastic infection caused by the bovine leukemia virus (BLV). BLV infection hinders the function of the immune system and induces other diseases, which negatively affects the performance and health of the infected cows. As the first line of defense against invading foreign pathogenic microorganisms, polymorphonuclear neutrophil (PMN) plays a vital role in the immune system of dairy cows. However, research on the effect of BLV infection on the immune function of PMN in dairy cows is scarce. Therefore, this experiment aimed to elucidate the effects and effect mechanisms of BLV infection on the immune function of PMN in dairy cows with different BLV provirus loads by detecting the chemotaxis, migration, adhesion, phagocytosis, respiratory burst function, and the formation of NETs. The experimental results showed that BLV infection had no significant effect on the phagocytosis of PMN but inhibited their migration and respiratory burst function, and the effects were closely related to the BLV provirus load. Under high BLV provirus load, PMN produced large amounts of NETs, chemokine CXCL7, adhesion molecule CD18, and pro-inflammatory factors IL-8 and TNF-α, triggering inflammatory responses and tissue damage. The results of this study provide a theoretical basis for ensuring healthy immune function in dairy cows.